A Study of the Star Clusters’ Population in the Giant Molecular Cloud G174+2.5 - Tatyana A. Permyakova; Giovanni Carraro; Anton F. Seleznev; Andrej M. Sobolev; Dmitry A. Ladeyschikov; Maria S. Kirsanova (The Astrophysical Journal)
We study the structure, interstellar absorption, color–magnitude diagrams (CMDs), kinematics, and dynamical state of embedded star clusters in the star-forming region associated with the giant molecular cloud G174+2.5. Our investigation is based on photometric data from the UKIDSS Galactic Plane Survey catalog and astrometric data from the Gaia DR3 catalogs. First, we recover all the known embedded clusters and candidate clusters in the region using surface density maps. Then, for the detected clusters, we determine their general parameters: the center positions, radii, number of stars, and reddening. To evaluate the reddening, we use both the NICEST algorithm and the Q -method. Both methods produce consistent extinction maps in the regions of the four studied clusters. However, the Q -method yields a much smaller color scatter in the CMD. For four clusters in particular (S235 North-West, S235 A-B-C, S235 Central, and S235 East1+East2), we were able to compute individual membership probabilities, the cluster distances, the cluster masses, and their average proper motions. By building on these results, we have studied the clusters’ kinematics and dynamics. Moreover, we estimate the mass of the gas component and the star formation efficiency in the regions of these four clusters. Finally, we provide an estimate of the total energy of the stellar and gas components in the area of these four clusters to determine whether the clusters are bound (here, we consider a “cluster” as the system “stars + gas”). The gravitational bound strongly depends on the region for which we estimate the gas mass. If we consider the mass of the entire cloud, all these four clusters turn out to be bound.